Mindenki másképp egyforma? : stratégiai fókuszpontok mintázata a piaci szerkezet tükrében - Katona, Norbert (Közép-Európai Közlemények, 2016)
In my doctoral research I examine the specific characteristic features of strategic management in case of domestic monopoly entities. While scientific interest has been primarily focused on small and medium-sized competitive or even globalized, crossing-boundaries giant companies and enterprises, there are only a few results known for the special regularity of strategic management of market-leader companies operating under monopoly or oligopoly market structure. Research described in this paper assumes the confirmed, already scientific proven link between strategy and marketing activities of organizations. Due to secondary statistically analyses of recent survey for the Hungarian Association for Marketing, specific strategic key points has been outlined, based on data came from more than 150 domestic enterprises of different size and operating in different market position and structure. As a result, this paper has confirmed for the market-leader monopolies and oligopolies the phenomenon of “turning inwards” as a strategic key-pattern, secondly weak links to the external, professional environment and thirdly detected the impact of absence of compulsion for the future; witch symptom is firmly linked to the phenomenon of “monopoly consciousness”, as well.